Do avian ticks (Ixodes hirsti) influence host phenotype in New Holland honeyeaters (Phylidonyris novaehollandiae)?. Issue 1 (2nd January 2017) - Taggart, Patrick L.; Schultz, David
ABSTRACT: Parasites can impact on host phenotype, causing adverse population changes. In avian populations, increased feather asymmetry as a consequence of parasitism is one example of parasites impacting host phenotype. Feather asymmetry can be important in sexual selection, reproductive success and survival, but relationships between feather asymmetry and measures of survival remain unclear. Previous studies have demonstrated these relationships in avian populations through experimental manipulation of parasite loads, but few studies have documented this relationship under natural levels of parasite infestation. We mist-netted 288 adult New Holland honeyeaters ( Phylidonyris novaehollandiae ) from 12 sites across South Australia to test for a relationship between ticks ( Ixodes hirsti ) and tail feather asymmetry, and tail feather asymmetry and body condition. Tick prevalence was 15% and intensity varied between 1 and 16 ticks. Tail feather asymmetry did not differ for birds according to their level of tick intensity, or body condition score. At this level of intensity, ticks are unlikely to have had implications for survival over the 4-year study period. Ground feeding and/or nesting birds are potentially exposed to higher levels of tick intensity and would be more suitable for studying the pathogenic effects of I. hirsti .